THE CONCEPT OF THE SHADOW ECONOMY AND SOME RECOMMENDATIONS FOR ITS ELIMINATION (Web of Discoveries: Journal of Analysis and Inventions, 2025)
In this article, the authors theoretically justify the term “shadow (fake) economy,” which is considered a form of the hidden economy in the official sector, and systematize its manifestations. Attention is also paid to the economic consequences of the shadow economy. The authors have developed their own scientific proposals and conclusions on preventing and eliminating the shadow economy.